Sharia Review of Online Sale and Purchase of Gold on Antam Website - Hidayat, Roni (Yayasan Mitra Peduli Indonesia, 2025)
Presently, people are increasingly interested in investing in gold, a stable financial instrument purchased at Antam. This secured and efficient website provides online gold sale and purchase services to the public, with delivery through boutiques and couriers. However, the transaction method compliance questions with Sharia principles because gold is delivered several days after payment, which has the potential to conflict with the concept of Yadan bi Yadin. This research aims to analyze whether online gold sale and purchase on Antam website is in accordance with the concept of Fiqh Muamalah and Maqashid Sharia. Data were collected from preliminary sales and analyzed using the content method. The result showed that online gold sale and purchase at Antam, does not conflict with the principle of Yadan bi Yadin, because non-cash is permitted, provided gold is not used as an official means of exchange (money) and the transaction meets the pillars and conditions of Salam sale and purchase. Based on the perspective of Maqashid Sharia, this service fulfills the objectives of Sharia. In conclusion, the practice of sale and purchase gold online on the official Antam website is in accordance with Sharia.